Textile Industry Waste Pollution in the Konto River: A Comparison of Public Perceptions and Water Quality Data - Adjid, Galang Ayuz Firstian Adjid; Kurniawan, Andi; Nazriati, Nazriati (Graduate School, Universitas Brawijaya, 2022)
Textile industry production activities in one of the Badas areas can have implications for the occurrence of dye liquid waste pollution in the Konto river flow. This implication leads to the public perception that there has been river pollution from textile dyeing liquid waste. In this case, public perceptions need to be analyzed as a form of river environmental monitoring activities. Therefore, public perceptions of pollution were compared with actual water quality data, especially related to dyes in river water, to link public perceptions with environmental resource management efforts. This study aims to analyze public perceptions of textile dye waste pollution and compare the analysis results with the river water quality analysis. Analysis of river water quality (dye content, BOD, COD) was conducted at five sampling points in Badas, Kuwik, Balungjeruk, and Wonorejo villages. Public perception was measured descriptively through interviews with respondents referring to the Slovin method. The analysis of public perceptions shows that the Public considers that there has been pollution of river water, mainly due to textile industry waste, along the Konto River. The results of the water quality analysis showed that dye concentrations were found at four sampling points except for Wonorejo Village. This result shows that the correlation between public perception and data on dye contamination only occurs in Badas, Kuwik, and Balungjeruk villages. In addition, the BOD/COD ratio indicates that pollution has occurred at all observation points in this study. Keywords: Aquatic Ecosystem, Dyes, Pollution, Public Perception, Waste.